Pengaruh Struktur Modal Terhadap Rentabilitas Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2013 - Nisa', Fitria Khairun, Dr. Anton Agus Setyawan, S.E., M.Si (2016)
Rentability in the world of banking represent old stuff matter. Where rentability (earning) represent one of the used criterion by banking management in assessing health bank. Intention of this research that is to analyse and give empirical evidence how far capital structure role in influencing rentability company banking. In this case capital structure variable measured with ratio equity to debt (DER), while rentability measured with assets on return (ROA), equity on return (ROE), margin profit (PM), and margin profit net (NPM). Population in this research banking finance service firm which enlist in Effect Exchange Indonesia (BEI) Period 2013. Method determination of sampel in this research determined by using sampling purposive method. Pursuant to criterion which have been determined by hence got counted 20 company of banking taken as sampel. Research data represent sekunder data with section cross data type in the form of period financial statement data 2013 which is obtained is Indonesian Capital Market Directory (ICMD) 2014. Examination hypothesis in this research use technique analyse linear regresi modestly and hypothesis test constructively SPSS software 16. Where examination hypothesis use signifikansi storey level equal to 0,05. Pursuant to result of research known that capital structure in the form of DER have an effect on by signifikan to rentability company of banking which enlist in Effect Exchange Indonesia period 2013 which measured with ROA, PM, and NPM. While capital structure in the form of DER don't have influence which signifikan to rentability ratio which is in the form of ROE. This matter is shown with result of linear regresi analysis modestly that is equation of Y1=4,505-0,330X; Y2=18,071-0,396X; Y3=0,463-0,028X; and Y4=0,376-0,024X. Where matter this means that all changes in one set of capital structure will cause change rentability in the form of ROA equal to 0,330%; ROE equal to 0,396%; PM equal to 0,028%; and NPM equal to 0,024%. By simultan known that ROA variable, PM, and NPM influenced by DER with signifikansi each of 0,002 for the ROA, 0,004 for the PM, and 0,010 for the NPM. While by simultan ROE variable not influenced by DER known by ROE variable signifikansi value equal to 0,478. Is there by suggested to researcher hereinafter to lengthen duration research into and add the amount of sampel company of larger ones and more immeasurable, and also use the more finance ratio in prediction rentability.